Influence of COVID-19 Pandemic on the Learners’ Academic Performance in Government Aided Primary Schools in Industrial City Division Mbale City - Wabusa Milly Becca (Uganda Christian University, 2024)
This study examined the influence of Covid-19 pandemic on the learners’ academic performance in primary schools in Industrial City Division, Mbale City. Evidence abounds of the influence of the pandemic on the learners in Mbale City. The general purpose of the study was to examine the influence of Covid-19 pandemic on the learners’ academic performance in primary schools in Industrial City Division, Mbale City. Specifically, the study sought; i) to examine the psychological influence of Covid-19 pandemic on the academic performance of learners, ii) to analyse the social influence on the academic performance of learners in Industrial City Division, Mbale City, iii) to assess how Covid-19 can be mitigated. The study adopted the descriptive research design. Data was analysed using self-administered questionnaires and interviews. It contained the response rate, demographic characteristics of the respondents and the data already existing and the information collected, The study was conducted in 04 selected primary schools in Industrial City Division, Mbale City. population of 131 respondents who comprised; 05 head teachers, 080 learners, 024 teachers and 01 education officer. In each school, the head of the school was interviewed together with the City education officer. The total number of respondents was 097 as per Kjercie and Morgan Population Table. Both Random and Purposive sampling techniques were employed to collect data in the Division. Data was collected by the researcher who developed three instruments; questionnaire, Interview Guide method and Data Quality Control for the teachers, school heads and learners respectively. The instruments were validated by three experts and both of them were from the Department of Education. The reliability coefficient that ranged between; 0.98, 0.99, 0.94, 0.88, and 0.92 was used to judge the validity and reliability of the instruments. The respondents were asked to examine the psychological effect of Covid-19 pandemic on academic performance of learners. In line with the above suggestions Covid-19 pandemic can be truncated and this requires a joint effort. The results show that what should mitigate the effects of the pandemic are; Cognitive Behavioral Therapy, vaccination, psychological assistance, reporting domestic violence and talking to children. This too calls for the school heads, educational officers, educationists and education stakeholders to carry out sensitization on how to cope with the pandemic. It was recommended in relation to the effect of Covid-19 pandemic on the academic performance of learners in Industrial City Division, Mbale City was made; Sensitisation of parents and teachers by the health workers and other experts should be carried out with regard to their role and responsibility to do counselling. Government to provide vaccines of children from 6 years of age and strengthen legal and policy framework that allows that the constitution of vaccination for all. Teachers and parents whose learners are have been affected by the Covid-19 pandemic to try to counsel them and make them understand that Covid-19 had not come to stay. The religious leaders on top of church sessions should make an effort of extending the lessons to Christians with the Covid-19 pandemic. They should also invite Covid-19 task force to continue speaking to their congregations. Financial empowerment of parents is a key factor since most homes were financially hit. This will help parents to provide for their children other than sending them to sell their bodies for food. Finally, the researcher acknowledges that this research is not the end of the influence of Covid-19 pandemic on the learners’ academic performance. It is recommended that further research should be undertaken in both private and government schools, urban and rural to have a comparative analysis of what goes on in these settings.